2018
DOI: 10.20944/preprints201812.0092.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Development of a Novel Staging Model for Affective Disorders Using Partial Least Squares Bootstrapping: Effects of Lipid-Associated Antioxidant Defenses and Neuro-Oxidative Stress

Abstract: Although, staging models gained momentum to stage define affective disorders, no attempts were made to construct mathematical staging models using clinical and biomarker data in patients with major depression and bipolar disorder.The aims of this study were to use clinical and biomarker data to construct statistically-derived staging models, which are associated with early lifetime traumata (ELTs), affective phenomenology and biomarkers.In the current study, 172 subjects participated, 105 with affective disord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 92 publications
0
21
0
Order By: Relevance
“…The results of the current study show that not only schizophrenia [5,11], but also MNP is accompanied by a simultaneous activation of the IRS and the CIRS whereby CIRS products released during an immuneinflammatory response attenuate the IRS. Moreover, previous research showed that MNP is characterized by specific deficits in the CIRS, as for example lowered levels of natural IgM responses to OSEs including malondialdehyde and azelaic acid [6,7,28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the current study show that not only schizophrenia [5,11], but also MNP is accompanied by a simultaneous activation of the IRS and the CIRS whereby CIRS products released during an immuneinflammatory response attenuate the IRS. Moreover, previous research showed that MNP is characterized by specific deficits in the CIRS, as for example lowered levels of natural IgM responses to OSEs including malondialdehyde and azelaic acid [6,7,28].…”
Section: Discussionmentioning
confidence: 99%
“…SNP and MNP are both defined by different neurocognitive and neuro-immune features with MNP being the more severe illness characterized by IRS activation and deficits in the CIRS, including in natural IgM [6]. Moreover, in MNP, indices of immune activation coupled with deficits in the CIRS explain a large part of the variance in executive functions, memory and attention deficits, as well as psychotic, hostility, excitation, mannerism (PHEM) and negative symptoms [28,29]. Nevertheless, no studies have examined the neuro-immune fingerprint of MNP or deficit schizophrenia in association with its phenomenology using M1 macrophage cytokines in combination with chemokines such as CCL-2 and CCL-11.…”
Section: Introductionmentioning
confidence: 99%
“…Another finding of this study is that women show increased levels of peroxides and IgM to NOW and NO-arginine indicating that ROS/RNS and nitrosative stress may in part contribute to sex differences in depression and BP1 for example to the increased incidence of depression in females. 8 Such effects could be associated with increased early life trauma and other psychosocial triggers that are associated with nitro-oxidative processes and with staging of depression and mood disorders.…”
Section: Discussionmentioning
confidence: 99%
“…It is understood that MDD and BP disorder are progressive disorders whereby increasing recurrent depressive/manic episodes and suicidal behaviors are associated with disabilities, lowered quality of life, neurocognitive decline and increased suicidal ideation and suicide attempts. 8 Furthermore, a new staging model of MDD and BP disorder indicates that this staging dimension (recurrent episodes and recurrent suicidal behaviors, increasing disabilities and lowered quality of life) is strongly associated with deficits in paraoxonase 1 (PON1), a strong antioxidant, and indicants of increased oxidative stress including aldehyde formation and protein oxidation. 8 Activated immune-inflammatory and oxidative pathways are usually accompanied by increased nitrosylation of proteins.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation